Analysis of Antibiotic Resistant Gene from Microbial Isolates of Chlorinated Water - Ramsha Essa, Naaz Abbas,Sania Mazhar, Sana Riaz, Saira Ashfaq, Abad Ali Nadeem, Ishrat Perveen, Quratulain Syed, Yasar Saleem, Syed Hussain Abidi, Tariq Javed (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Chlorination is commonly used to disinfect water as it efficiently kills the microbe by destroying its membrane enzyme. Although some gram positive bacteria that are antibiotic resistant also show resistance against chlorine. This resistance may be due to some unique protein or maybe confer by the antibiotic resistant genes. Aim: To analyze the relationship between antibiotic and chlorine resistance to verify the role of antibiotic resistant genes in chlorine resistance. Methodology: VAN-A and TET-O genes were amplified from a chlorinated water sample and computation analysis was carried out to analyze these proteins. Docking was performed to quantify binding affinity between resistant genes and hypochlorite ligand. Results: Low binding energy confirmed the incompetency of chlorine and antibiotics against resistant genes. Expression analysis of PET-28 GFP recombinant plasmid under antibiotic and chlorine stress indicated successful expression by J express. Conclusion: Computational study proves that antibiotic resistant gene has a role in conferring resistance against chlorine. Keywords: Antibiotic resistance, chlorine resistance, molecular modeling, recombinant plasmid, hypochlorite